A Dynamic Allocation Method on Virtual Resource in Cloud Call Center - Ying Ling; Wei Xu (Dianxin kexue)
Business platform built on cloud computing cloud resource pool call center system, can not only do load balancing control at the operational level, realize intelligent call center scheduling and resource allocation, automatically do the equalization processing of incoming load and the agent check-in load, support word service, unified scheduling of service resources and unified operation and management of business, but also need to achieve dynamic resource allocation stretching because the cloud call center business systems deployed in the cloud data center resources pool can be shared with other applications infrastructure. A cloud call center system for dynamic virtualized resources allocation method was presented, which determines the operation of the system resource pool dynamically allocates resources based on the upper application resource pool. The method contains virtual resource dynamic allocation request trigger mechanism initiated by the cloud call center system, the interfaces of cloud call center system and resource management platform for dynamic allocation of resources and so on.